Developmental roles of protein N‐terminal acetylation. Issue 14 (15th June 2015) - Silva, Rui D.; Martinho, Rui G.; Van Damme, Petra; Gevaert, Kris
<x xml:space="preserve">Abstract</x> Discovered more than 50 years ago, N‐terminal acetylation (N‐Ac) is one of the most common protein modifications. Catalyzed by different N‐terminal acetyltransferases (NATs), N‐Ac was originally believed to mostly promote protein stability. However, several functional consequences at substrate level were recently described that yielded important new insights about the distinct molecular functions for this modification. The ubiquitous and apparent irreversible nature of this protein modification leads to the assumption that N‐Ac mostly executes constitutive functions. In spite of the large number of substrates for each NAT, recent studies in multicellular organisms have nevertheless indicated very specific phenotypes after NAT loss. This raises the hypothesis that in vivo N‐Ac is only functionally rate limiting for a small subset of substrates. In this review, we will discuss the function of N‐Ac in the context of a developing organism. We will propose that some rate limiting NAT substrates may be tissue‐specific leading to differential functions of N‐Ac during development of multicellular organisms. Moreover, we will also propose the existence of tissue and developmental‐specific mechanisms that differentially regulate N‐Ac.